Leitura literária : estratégia para formar leitores de folhetos de cordel - Costa, Josivânia da Silva Santos (2018)
This work presents a pedagogical proposal of literary reading for a class of the 7th Year of Elementary School II of a public school, in the city of Pinhão, in the state of Sergipe, with the cordel Proezas de João Grilo by João Ferreira Lima, considering the made popular culture permeated by aspects of humor present in his narrative. The perception of a reality marked by unsatisfactory indexes in the Portuguese language proficiency of public school students in the country aroused the interest of developing a practice of subjective reading aimed at contributing to the formation of the taste for reading. The work consists of bibliographical research and action research, for the purpose of investigating the pedagogical practice itself. It was based on the perspective of the fruitful understanding, in the subjective reading, proposed by Jauss and Rouxel; in the representativity of the cordel genre, marked by Márcia Abreu and Ruth Terra, and in the liberating character of humor, evidenced by Freud, Travaglia and Possenti, among others. As an intervention approach, the work proposes cordel workshops. The genre, suggested by the National Curricular Parameters (PCNs) for working with this modality of teaching, is the originator and popularizer of popular culture. The development of the workshops resulted in the involvement of the student with the handout, thus providing students with the appropriation and re-signification of the text inserted in popular culture, in a process that constitutes the so-called "reader's text", according to Anne Rouxel.